PENGARUH KINERJA PELAYANAN CUSTOMER SERVICE TERHADAP LOYALITAS PELANGGAN - Magdalena, Maria; Erida, Erida; Bhayangkari, Sylvia Kartika Wulan (Jurnal Dinamika Manajemen, 2018)
This study aimed to determine the effect of customer service performance on customer loyalty in Astra Credit Companies Jambi. This study employs survey research using a questionnaire instrument. The samples taken in this study are a customer in Astra Credit Companies Jambi. The data analysis technique uses multiple regression to test the absolute value of the difference. This study shows that customer service performance (believable, enthusiastic, responsive, the best solution, professional) affects customer loyalty. The impact of customer service performance (credible, passionate, responsive, the best solution, professional) on customer loyalty has powerful coefficient determination. Based on this study, the advice that the authors can give is that the Astra Credit Companies are expected to increase the dimensions of reliability further because this dimension is the average lower than another dimension, namely by expanding the knowledge of customer service officers on work procedures concerning all customer needs who came to his desk and more able to interact with customers.